Guidelines to the THM - Spartà Roberta (EPJ Web of Conferences)
Guidelines to the use of the indirect Trojan Horse Method to get cross sections of interest for nuclear astrophysics are given, using the example of the d+d reactions of interest for the Big Bang Nucleosynthesis model.